Evolution of the levels of soluble interleukin-2 receptors during Plasmodium falciparum and P. vivax malaria. - Deloron, P (1989)
Increased levels of soluble interleukin-2 receptors (IL-2R) in serum were observed in both Plasmodium falciparum- and P. vivax-infected individuals compared with nonparasitemic subjects. Clinical symptoms of P. falciparum malaria were associated with higher levels of soluble IL-2R. Temporal evolution in serum of IL-2R during the course of a malaria attack mimicked the kinetics of soluble IL-2R under experimental conditions.